ANALISIS YURIDIS PENDAFTARAN TANAH DI ATAS LAHAN TANAH YANG DI ALIH FUNGSIKAN DARI KAWASAN HUTAN PASCA KEPUTUSAN MENTERI NOMOR 579/MENHUT-II/2014 (STUDI PADA KABUPATEN LABURA) - PERKASA ALAMSYAH TANJUNG (PREMISE LAW JURNAL, 2017)
The results show that, the forest conversion stipulated in Decree No. 579/Menhut-II/2014, does not completely answer the problem of the forest conversion under the Decree no. 44/Menhut-II/2005 in some regions in North Sumatera, especially in Labura Regency and its sub-districts. The status of the land which is converted into other Land Use, the coordinate point, or the forest conversion borders are allocated for Other Land Use as regulated in the Decree No. 579/Menhut-II/2014, the reduction of forest is not supposed to reduce the old area that has long been occupied and managed by the society, either the land has title certificate or not, by either individual or limited liability company who has long occupied the land. Thus, the confusion about which land title has been registered and which will be creates confusion in the society. Keywords: Land Conversion, Forest and Cultivation Area